Literatur Review: Pengaruh Sales Growth dan Good Corporate Governance Terhadap Financial Distress - Hidayani, Sindy Aprilia; Candra, Yulian Ade (Shofanah Media Berkah, 2026)
The financial stability of companies in Indonesia is a major concern, especially post-pandemic and amidst global economic uncertainty, where many large companies are facing financial difficulties and the risk of bankruptcy. This study aims to analyze the effect of Sales Growth and Good Corporate Governance (GCG) on Financial Distress through a literature review approach. This study uses a quantitative method with a literature review approach, examining 50 articles published in the last ten years (2018-2025) from Google Scholar. Articles were selected based on the keywords Sales Growth, Good Corporate Governance, and Financial Distress. The analysis results show varying (and inconsistent) findings regarding the effect of Sales Growth and GCG on Financial Distress. Although most studies indicate that GCG and Sales Growth have a significant influence aimed at overcoming financial distress, some studies find no significant effect. This variation underscores the complexity of the relationship between these factors and a company's financial distress.